Desolation angels : a novel [compact disc, unabridged] - Kerouac, Jack, 1922-1969 (Blackstone Publishing, 2025)
After spending two months in the summer of 1956 as a fire lookout on Desolation Peak in the North Cascade Mountains of Washington, Kerouac's fictional self Jack Duluoz comes down from the isolated mountains to the wild excitement of the bars, jazz clubs, and parties of San Francisco, before traveling on to Mexico City, New York, Tangiers, Paris, and London.